Noninvasive evaluation of pulmonary hypertension using the second heart sound parameters collected by a mobile cardiac acoustic monitoring system - Huang, Jingjuan; Zhang, Weiwei; Fu, Wenxia; Le, Jiawei; Qi, Yiding; Hou, Xumin; Pan, Xin; Li, Ruogu; He, Ben (Frontiers in Cardiovascular Medicine, 2023)
Background Pulmonary hypertension (PH) is linked to higher rates of morbidity and mortality worldwide. Early diagnosis of PH is important for clinical treatment. The estimated pulmonary artery systolic pressure (ePASP ≥ 35 mmHg) measured by echocardiography helps screen PH patients. In this paper, we report a novel PH screening method through a mobile cardiac acoustic monitoring system. Methods In the retrospective study, patients admitted to our hospital between January 2022 and April 2023 were classified into PH and control groups using ePASP and compared with acoustic cardiographic parameters. According to ePASP, PH severity was classified as mild, moderate, and severe. We analyzed the first and second heart sound (S1, S2) characteristics, including amplitude (S1A, S2A), energy (S1E, S2E), and frequency (S1F, S2F). Results The study included 209 subjects, divided into PH (n = 121) and control (n = 88) groups. Pearson correlation analysis confirmed the positive correlation between S2F and ePASP. The diagnostic performance of S2F as assessed by the area under the ROC curve was 0.775 for PH. The sensitivity and specificity of diagnosing ePASP ≥ 35 mmHg when S2F ≥ 36 Hz were found to be 79.34% and 67.05%, respectively, according to ROC analysis. Severity classification was performed using S2F, the area under the ROC curve was 0.712–0.838 for mild PH, 0.774–0.888 for moderate PH, and 0.826–0.940 for severe PH. Conclusions S2F collected by the mobile cardiac acoustic monitoring system offers a convenient method for remote PH screening, potentially improving PH management and outcomes.